(untitled) - Ballast, David Kent (Hoboken, N.J., 2007)
This book remains the only comprehensive reference to the thousands of industry standard tolerances for the manufacture, fabrication, and installation of construction materials and components-- including all-important accumulated dimensional variations.
Keywords: Kết cấu kỹ thuật,Dung sai (Kỹ thuật),Xây dựng,Structural engineering,Tolerance (Engineering),Building; Thông tin chi tiết,Details